Язык как орудие дегуманизации в языковом пространстве вооруженного конфликта в Украинe - Bortnowska, Paulina (Studia Rossica Posnaniensia, 2024)
The armed conflict in Ukraine, continuing in its culminating form since 24.02.2022, exists in two dimensions – on the battlefield and in the information space. In this second dimension, the main role is played by language, used as a potent weapon, one of the prominent functions of which is that of dehumanization. By violating the norms of constructive public communication, the creators of this discourse – journalists, opinion leaders, activists, politicians – activate the destructive potential of language. The dehumanizing discourse of the armed conflict in Ukraine, however, has not yet received a vigorous linguistic elaboration. The aim of this article is to raise this complex and important issue. By giving various examples of acts of linguistic dehumanization observed in the widely understood linguistic space of the armed conflict in Ukraine, the author identifies the main directions of dehumanization discourse within the Russian-Ukrainian linguo-cultural space. The author’s provided examples of dehumanizing statements facilitate the identification of both explicit and subtle dehumanization techniques prevalent within this discourse. At the same time, public figures are actively involved in the retransmission of dehumanizing content, which significantly affects the dynamics of this discourse and increases the range of its potential active and passive participants.